Equilibrium interest rate and financial transactions in post-Keynesian models. Pointing out some overlooked features - Angel Asensio (Intervention. European Journal of Economics and Economic Policies, 2011)
The paper argues that beyond the deviations of the long-term interest rate the monetary authority may cause, it is the rate determined by the market conventional expectations that prevails eventually. Lasting influence requires the authority to be capable of changing the market conventional expectations, not only refinancing conditions. The paper also explores the implicit financial transactions behind interest rate determination in post-Keynesian simple macro-models. It points out symmetry between the money and finance markets in equilibrium models. As a consequence of endogenous money, the finance market cannot but clear along with the money market, which sheds light on the rejection of the 'loanable funds' theory. In disequilibrium business cycle models, on the other hand, the symmetry is between the financial and goods markets, as in the 'loanable funds' theory.
Keywords: E12; E40; E43; E44; E51; 330; endogenous money; equilibrium interest rate; convention; finance; post-Keynesian economics